Developmental trajectories in psychiatric disorders: does substance/alcohol use moderate the effects of affective temperaments as moderators of age at onset? A study in post-acute, hospitalized patients with psychotic or DSM-5 bipolar or major depressive disorders. Issue 3 (1st July 2021) - Perrini, Filippo; Matrone, Marta; de Bartolomeis, Andrea; Montano, Antonella; Amici, Emanuela; Callovini, Gemma; Cuomo, Ilaria; de Persis, Simone; Lombardozzi, Ginevra; Battagliese, Gemma; Porrari, Raffaella; Kotzalidis, Georgios D.; et al.
Abstract: Background: Age-at-onset (AAO) affects psychiatric disorder outcome; substance (SUDs) or alcohol use disorders (AUDs) may influence their onset. Affective temperaments may affect early AAO and drug-use proneness. Objectives: To investigate whether SUD/AUD moderated temperamental effects in determining AAO of mental disorders. Methods: We included 300 post-acute inpatients with schizophrenia-spectrum and other psychotic (SSOPDs), major depressive (MDD) or bipolar (BD) disorders (168 men; mean age, 40.63 years ± 11.82 men, 43.21 years ± 12.69 women) with (N = 110) or without (N = 190) SUD/AUD. Patients completed cross-sectionally TEMPS-A. We carried moderation analysis with each regression-significant TEMPS temperament as independent variable, SUD/AUD presence/absence as dichotomous moderator, and AAO as dependent variable. Significance was set at p  < 0.05. Results: AAO was lower in patients with SUD/AUD diagnosis than in patients without (23.74 ± 10.09 vs . 27.73 ± 10.35, respectively, p  = 0.001, η2 = 0.034). SUD/AUD patients scored higher on the hyperthymic (10.22 ± 4.08, p  < 0.001, η2 = 0.069) and irritable (8.26 ± 4.69, p  < 0.01, η2 = 0.026) temperaments than nonSUD/AUD patients. Moderation analysis showed only direct effects of irritable (β = −0.55, p  < 0.005) and hyperthymic (β = −0.95, p  < 0.001) temperaments on AAO and no significant SUD/AUD and interaction effects. Limitations . Cross-sectional design. Conclusions: When irritable and hyperthymic traits prevail over other temperaments, AAO is earlier in SSOPDs, MDD, and BD. SUD/AUD presence/absence does not moderate the relationship between temperament and AAO.